STUDY OF RENAL FUNCTION TESTS IN THYROID DISORDER PATIENTS - VANITA SHARMA; USHYENDER SHARMA; BHARTI KAWATRA; J P BHARTIYA; H K WALIA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To analyse serum creatine, urea, fT3, fT4 and TSH among thyroid disorder patients. Method: 75 thyroid disorder patients were included in the study. Serum creatinine and blood urea were determined by the colorimeteric method using an autoanalyzer c311. Thyroid Profile-fT3, fT4, and TSH were estimated by chemiluminescence immunoassay. Serum creatinine and blood urea were found to be raised among hypothyroidisms. Results: The mean fT3=2.09, mean fT4= 0.88 and mean TSH=17.82μIU/ml, mean urea=72.32 mg/dl and mean creatinine=2.4 mg/dl. The highest creatinine value was 12 mg/dl and highest urea value among the hypothyroidism patient was found to be 180.4 mg/dl. Conclusion: Assessment of hypothyroidism and its effect on kidney will be helpful in early diagnosis and management of the patients